Delegation and coordination with multiple threshold public goods: Experimental evidence - Luca Corazzini; Christopher Cotton; Tommaso Reggiani (Queen's University, Department of Economics, 2019)
When multiple charities, social programs and community projects simultaneously vie for funding, donors risk miscoordinating their contributions leading to an inefficient distribution of funding across projects. Community chests and other intermediary organizations facilitate coordination among donors and reduce such risks. We explore such considerations by extending the threshold public goods framework to allow donors to contribute to an intermediary rather than directly to the public goods. We experimentally study the effects of the intermediary on contributions and successful public good funding. Results show that delegation increases overall contributions and public good success, but only when the intermediary is formally committed to direct funding received from donors to socially beneficial goods. Without such a restriction, the presence of an intermediary is detrimental, resulting in lower contributions, a higher probability of miscoordination, and lower payoffs.
Keywords: C91; C92; H40; H41; L31; 330; Delegation; threshold public goods; laboratory experiment; fundraising